Exercise as a multi-modal disease-modifying medicine in systemic sclerosis: An introduction by The Global Fellowship on Rehabilitation and Exercise in Systemic Sclerosis (G-FoRSS). Issue 3 (September 2021) - Pettersson, Henrik; Alexanderson, Helene; Poole, Janet L.; Varga, Janos; Regardt, Malin; Russell, Anne-Marie; Salam, Yasser; Jensen, Kelly; Mansour, Jennifer; Frech, Tracy; Feghali-Bostwick, Carol; Varjú, Cecília; et al.
Abstract: Systemic sclerosis (SSc) is a heterogeneous multisystem autoimmune disease whereby its main pathological drivers of disability and damage are vascular injury, inflammatory cell infiltration, and fibrosis. These mechanisms result in diffuse and diverse impairments arising from ischemic circulatory dysfunction leading to painful skin ulceration and calcinosis, neurovascular aberrations hindering gastrointestinal (GI) motility, progressive painful, incapacitating or immobilizing effects of inflammatory and fibrotic effects on the lungs, skin, articular and periarticular structures, and muscle. SSc-related impairments impede routine activities of daily living (ADLs) and disrupt three critical life areas: work, family, social/leisure, and also impact on psychological well-being. Physical activity and exercise are globally recommended; however, for connective tissue diseases, this guidance carries greater impact on inflammatory disease manifestations, recovery, and cardiovascular health. Exercise, through myogenic and vascular phenomena, naturally targets key pathogenic drivers by downregulating multiple inflammatory and fibrotic pathways in serum and tissue, while increasing circulation and vascular repair. G-FoRSS, The Global Fellowship on Rehabilitation and Exercise in Systemic Sclerosis recognizes the scientific basis of and advocates for education and research of exercise as a systemic and targeted SSc disease-modifying treatment. An overview of biophysiological mechanisms of physical activity and exercise are herein imparted for patients, clinicians, and researchers, and applied to SSc disease mechanisms, manifestations, and impairment. A preliminary guidance on exercise in SSc, a research agenda, and the current state of research and outcome measures are set forth.